Pengaruh Penerapan Pendekatan Etnopedagogi Dalam Pembelajaran Bahasa Indonesia - Sarira, Faskalia Senniaty; Baan, Anastasia; Gasong, Dina (CV. ITTC INDONESIA, 2024)
The aim of this research is to describe the influence of applying an ethnopedagogy approach in Indonesian language learning on improving student learning outcomes at SMP Negeri 4 Sesean Satap. The research was carried out using an experimental method. Data collection procedures were carried out using observation, tests, documentation and questionnaires. The data analysis method used in this research is a quantitative data analysis technique using a simple linear regression test. The results of this research indicate that the application of an ethnopedagogical approach in learning Indonesian has a positive effect on improving student learning outcomes at SMP Negeri 4 Sesean Satap. This is proven by the hypothesis test (t test) where the value is 0.00 <0.05 and the t value is 7.623> t table 1.693. These results are in accordance with the respondents' answers to the questionnaire who chose the answers strongly agree and agree.